The Impact of Cholesterol on Stroke Outcomes: A Cross-Sectional Analysis in Central Java - Maulani, Yulita; Toirov Abdukhamid Suvonovich; Emma Ismawatie; Asri Wulandari (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Stroke remains a leading cause of mortality and morbidity globally, with variations in subtypes and risk factors observed across populations. The role of cholesterol in stroke, particularly its association with ischemic and hemorrhagic subtypes, continues to be investigated. This study aimed to examine the relationship between cholesterol levels and stroke outcomes in a Central Javanese population. Methods: A cross-sectional study was conducted at hospitals in Central Java, Indonesia. Data were collected from medical records of patients diagnosed with ischemic or hemorrhagic stroke between January and December 2022. Demographic information, stroke subtype, and cholesterol levels were analyzed. Statistical tests were employed to assess the association between cholesterol and stroke outcomes. Results: The study included 68 patients (34 ischemic, 34 hemorrhagic). The majority of hemorrhagic stroke patients were female (52.9%), while ischemic stroke patients were predominantly male (64.7%). The mean cholesterol level for hemorrhagic stroke patients was 202.59 mg/dL, and for ischemic stroke patients, it was 190.26 mg/dL. Statistical analysis revealed no significant association between cholesterol levels and stroke subtype (p > 0.05). Conclusion: The findings suggest that cholesterol levels may not be a primary determinant of stroke subtype in this Central Javanese population. Further research is warranted to explore other potential risk factors and their interplay with cholesterol in influencing stroke outcomes.